PENERAPAN MODEL PEMBELAJARAN INKUIRI TERSTRUKTUR UNTUK MENINGKATKAN HASIL BELAJAR MURID SMP - Erlita Sekar Firdausi; Martini Martini (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
The low achievement of science learning outcomes in the material of temperature and heat, which is often below the minimum completion criteria, triggers the need for innovative learning methods that are more centered on active student involvement. The focus of the problem in this study is directed at testing the effectiveness of the implementation of the structured inquiry model in optimizing students' understanding of concepts and science process skills. The research steps were carried out through a quantitative approach with a one-group pretest-posttest design involving twenty-nine seventh-grade students at SMP Negeri 52 Surabaya. Crucial stages include observation of the implementation of learning, administration of initial tests, interventions through guided experiments, and final evaluations using validated multiple-choice instruments. The research findings show that all learning sessions were carried out perfectly with a very good category. Quantitatively, the results of statistical analysis prove a significant increase with a significance value below 0.000. The average student learning achievement jumped drastically from a score of 56.6 to 90, supported by the acquisition of an N-Gain value of 0.76 which places the effectiveness of this model in the high category. The main conclusion confirms that the structured inquiry model is highly effective in improving learning outcomes across the board because it facilitates meaningful, hands-on experiences in accordance with constructivist principles. The integration of systematic scientific inquiry has been shown to transform passive thinking patterns into more critical and analytical ones, contributing to the overall cognitive development of secondary school students.